The unraveling of scientism : American philosophy at the end of the twentieth century - Margolis, Joseph, 1924- (Ithaca, N.Y. : Cornell University Press, 2003)
"The Unraveling of Scienticism centers on the primary commitment of analytic philosophy through the twentieth century to what Margolis calls "scientism"--The conviction that an unyielding reductionism, applied universally but in an exemplary way in the sciences, can provide a convincing account of the most important philosophical puzzles of the human world, those centered on the nature of the objective world, our knowledge of reality, language, and human existence. Margolis examines the principal puzzles that the analytic movement has addressed and argues that in recent years its claims have been effectively stalemated, perhaps even defeated."--Jacket
First word : anticipation of a final reckoning -- Materialism by less than adequate means -- Incommensurability modestly recovered -- Restoring the bond between realism and truth -- The unraveling of scientism.
Includes bibliographical references (pages 153-173) and index.
Print version record.
JSTOR
Keywords: Analysis (Philosophy) -- United States -- History -- 20th century; Philosophy, American -- 20th century; Philosophie analytique -- États-Unis -- Histoire -- 20e siècle.; Philosophie américaine -- 20e siècle.; HISTORY -- United States -- 20th Century; Analysis (Philosophy); Philosophy, American; United States; Analytische Philosophie; Philosophie; USA; Analytische filosofie; Pragmatisme; 1900-1999; History